IDENTIFIKASI JENIS-JENIS EKTOPARASIT PADA IKAN LELE DUMBO (Clarias gariepinus) Identification of Ectoparasites in Dumbo Catfish (Clarias gariepinus) - Ayu Syahfitri Daulae; Dwi Suryanto; Desrita Desrita (AQUACOASTMARINE, 2018)
Dumbo catfish (Clarias gariepinus) is usually cultured with high density in pond. This fish is tolerant to low oxygen level and grow rapidly. However, in culture, this fish is often attached by some parasites. The purpose of this study is to find out what kinds of ectoparasites infect Dumbo catfish and to know dominant ectoparasitic infecting Dumbo catfish. This study was conducted from May until June 2017. This research was conducted with three repeated with the comparison of two ponds, then each pond is taken fish samples three pond fish samples were taken from two ponds with three reflication. Total sample were 18 fish. The result showed that Ichthyophthirius multifiliis, Trichodina, Chilodonella, Dactylogyrus,were dominant ectoparasites in the fish and water.Keywords : Catfish, Ectoparasitic.